Implementation Of University Community Engagement Work Culture In Strengthening Spritual Performance and Resilience of Employees in the Pandemi Era Case Study at Jember Islamic University East Java Indonesia - Halid, Ahmad (Proceedings of Annual Conference on Community Engagement, 2022)
This article wants to look very special in the work. Because hard -working employees are a must, and excellent achievement is measured by the employees' maximum performance and self -retention. The problem of this article is how the implementation of university community engagement work culture in strengthening spiritual performance and resilience of employees in the pandemic era case study at jember islamic university east java indonesia? This problem can be solved by descriptive qualitative methods, the data are collected by interview methods, observation, documentation and sharpened with emic data and ethical data as well as using data treanggulation. The result of this study is that (1) the maximum work result is work based on spiritual performance and resilience of employees so that it can trigger high productivity. (2) Build a high work awareness, peace and even satisfaction and high trust (3) apply organizational philosophy in shaping spiritual performance and resilience to all members of the organization.